Uncovering the Gaps and Linkages: Exploring Postpartum Mood and Anxiety Disorders and Experiences for Clinicians and Parents within One Northern Community - Christina, DeRoche; Anna-Liisa, Mottonen; Treva, Reed (Journal of Women's Mental Health, 2026)
The current research assessed gaps and barriers related to perinatal mental health service access by parents during COVID-19, as well as service providers’ knowledge and provision of PMAD services, in one Northern community, where rural and remote healthcare is a daily reality, and recruitment and retention of qualified professionals is a significant issue. Two mixed-methods surveys were designed, one to assess PMAD knowledge and service provision via a volunteer sample of service providers, and another to assess PMAD service need and access among a volunteer sample of new parents. Results indicated that many parents waited too long for services, and some parents in need of PMAD services didn’t receive them. Interestingly, higher-income parents were more likely than lower-income respondents to desire services and support for PMADs. Although most providers screened for, were trained in, and treated and/or referred patients with PMADs, they reported feeling as though they were working in silos, unaware of what other providers offered.
Keywords: maternal mental health; perinatal mood and anxiety disorders; service provider experiences; parent experiences; northern Ontario; post-pandemic experiences